Use of periodicals in the Filipiniana and Special Collections Division, University of the Philippines, Diliman Main Library, June 1987 to September 1988 - Ponseca, Zenaida R. 1957-
Based on the findings of the study, the following recommendations are made to improve the services rendered in the periodical collection of the Filipiniana and Special Collections Division of the University of the Philippines Diliman, Main Library: 1) a study be undertaken on why there have been few faculty members who used the periodical collection; 2) further study on the use of periodical literature be undertaken among the students of the College of Mass Communication; 3) periodical titles that have not been indexed be sent to the Bibliography and Indexing Division for indexing and for the Bibliography and Indexing Division to undertake a review of their internal policies and guidelines regarding indexing; 4) a review of the Index to Philippine Periodicals be undertaken to determine which periodical titles have been/are indexed; 5) the less or least used periodical titles are well as those with no lending activity should be temporarily relocated to a nearby storage area to give way to most frequently used titles; and 6) the Division's staff be given ample time to be well informed on current issues.